All-solid-state potassium-selective sensor based on carbon black modified thermoplastic electrode - Ozer, Tugba; Henry, Charles S. (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Thermoplastic carbon composite electrodes have been introduced by our group as novel electrodes with improved electrochemical properties and previously applied for accurate detection of biomarkers using voltammetric methods. Because of their exceptional properties, we hypothesized they would work well as potentiometric ion-selective electrodes as well. In this work, potassium selective thermoplastic electrodes (TPEs) were developed for potentiometric detection for the first time and applied in biofluids. TPEs were fabricated using mixture of polystyrene and polycaprolactone and two types of graphite (MG1599 and Nano19) for comparison, and modified with carbon black via drop-casting. Carbon black modification was optimized in the presence of various numbers of carbon black layers, while ion selective membrane components were optimized at different component ratios. Under optimized conditions, TPEs exhibited Nernstian response to K+ with sensitivity of 59.3 +/- 1.01 mV decade(-1) and near-Nernstian response with sensitivity of 56.8 & nbsp;+/- 1.7 mV decade(-1) within a linear range of 1.0 x 10(-4) M-1.0 x 10(-1) M with a LOD of 1.0 x 10(-4)-M for Nano19-and MG1599-based TPEs, respectively. The K (+)-selective TPEs demonstrated rapid response (4 s) and excellent stability, repeatability and reproducibility. The applicability of electrodes were shown in human pooled urine and artificial interstitial fluid samples with potassium ion concentrations ranging from healthy and unhealthy levels. Therefore, the electrodes could be used in healthcare applications for accurate detection of K (+) exists in complex matrix and can be easily adapted to simultaneously monitor other ions for diagnosis of diseases due to miniaturization of TPEs. (C)& nbsp;2021 Elsevier Ltd. All rights reserved.
Keywords: Ion-selective electrode; Potassium; Solid-contact; Carbon black; Potentiometric sensor; ELECTROCHEMICAL SENSOR; ION; CONTACT; COMPOSITE; LAYER; GRAPHENE; URINE; K+; TRANSDUCER; NANOTUBES; Electrochemistry